Physical Medicine and Rehabilitation Residency Quality Improvement and Research Curriculum: Design and Implementation. (February 2021) - Grover, Prateek; Volshteyn, Oksana; Carr, David B.
Abstract : Abstract: Physical medicine and rehabilitation residency programs do not demonstrate a uniform level of training and mentorship for resident scholarly activities related in part to variable utilization of standardized curricula. The aim of this study was to design, develop, implement, and evaluate a structured Quality Improvement and Research Curriculum for a physical medicine and rehabilitation residency program in academic year 2015 using standardized methodology. A combination of five-phase project-lifecycle and six-step medical-curriculum development methodologies was used to integrate existing resources into five institutional domains: (1) Patient Safety and Quality Improvement Program ; (2) Research Mentorship Program ; (3) Rehab in Review ; (4) Publication and Presentation Resources, and (5) Research and QI Lecture Series . Dedicated resident-faculty teams were created for individual domains and for the overall curriculum. Written materials developed included scope documents, reporting forms, and tracking tables. A dedicated webpage on the department website served as an accessible resource. A bimonthly Updates newsletter highlighted ongoing resident achievements. Program and resident outcome metrics were evaluated at the mid and end of academic year 2015. Excellent resident and good faculty participation in the curriculum was observed. Resident publication and presentation productivity improved. Time was the biggest barrier to success. Key factors for success included phased implementation, dedicated teams, scope clarity, accessible resources, personnel support, resident champions, and faculty mentorship.